Multifetal pregnancy reduction outcomes from triplets to singletons and twins - Zeynep Gedik Özköse; Süleyman Cemil Oğlak; Züat Acar; Şeyhmus Tunç; Salim Sezer; Osman Samet Günkaya; İsmail Özdemir (Perinatal Medicine Foundation, 2022)
Objective: To study the obstetric and neonatal outcomes of reduction to singleton and twin pregnancies by multifetal pregnancy reduction (MPR) in patients with triplet pregnancies. Methods: The multifetal reduction was performed in 27 patients with triplet pregnancies. Fourteen patients were reduced to singleton pregnancies and 13 patients to twin pregnancies. Obstetric and neonatal outcomes were compared between the two groups. Results: The mean gestational age at the time of the procedure was 12.43±0.76 weeks in patients reduced to singleton pregnancies and 12.08±0.64 weeks in those reduced to twin pregnancies. The most common complications of the procedure were abdominal pain (21.4%) in women with singleton pregnancies and both the presence of abdominal pain and vaginal bleeding (30.8%) in women with twin pregnancies. Gestational age at birth (33.07±5.73 versus 35.78±6.14 weeks, p=0.009) and neonatal birth weight (1998.46±808.07 versus 2765±803.03 gram, p=0.003) was significantly higher in the group reduced to singleton pregnancies than in twin pregnancies. Conclusion: The MPR procedure is a good and acceptable option for patients with multiple pregnancies of three or more children. Multifetal pregnancy reduction of triplets to singletons is associated with better pregnancy outcomes such as birth at higher weeks of gestation and higher neonatal birth weight than MPR of triplets to twins.